lg x/10=-2-2lg x
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 15:47:16
lgx/10=-2-2lgxlgx/10=-2-2lgxlgx/10=-2-2lgxlg(x/10)=-2-2lgxlgx-lg10=-2-2lgxlgx-1=-2-2lgx3lgx=-1lgx=-1
lg x/10=-2-2lg x
lg x/10=-2-2lg x
lg x/10=-2-2lg x
lg(x/10)=-2-2lgx
lgx-lg10=-2-2lgx
lgx-1=-2-2lgx
3lgx=-1
lgx=-1/3
x=1/[³√(10)]
lgx-lg10=-2-2lgx
lgx-1=-2-2lgx
lgx=-1/3
x=10的-1/3次方
lg x/10=-2-2lg x
(lg5)^+lg 2 x lg 50=?
lg(x^2-8x+9)=lg(3-x)
{x|lg(x-2)
lg(2-2x)-lg(x+1)
不等式lg(x-3)+lg(x-2)
lg(2-x)-lg(x-1)>0
求解方程lg(x+3)+lg(x-1)=lg(x^2-2x-3).
若lg(x-1)+lg(3-x)=lg(2-x),则x=
lg(2-x)+lg(3-x)=lg12 lg(x^2+75)-lg(x-4)=2lg(2-x)+lg(3-x)=lg12第一题lg(x^2+75)-lg(x-4)=2 第二题
解方程:lg(x+1)+lg(x-2)=lg4
解方程:lg(x-1)+lg(x+2)=1
解方程lg(x+1)+lg(x-2)=lg4?
函数f(x)=lg(lg x-2)的定义域
lg(10x+9)-2
lg(x-1)=2
对数函数方程~lg(12-5x)-lg(3+2x)=lg(4-3x)-lg(2x+1)
2lg(2x-1)=lg(-2x+7)+lg(x+1)